2011
DOI: 10.3810/pgm.2011.11.2500
|View full text |Cite
|
Sign up to set email alerts
|

Updating the Role of Natriuretic Peptide Levels in Cardiovascular Disease

Abstract: Heart disease affects 1 in 3 individuals in the United States, and the prevalence of heart failure (HF) is increasing exponentially. Although our understanding of the disease progression of congestive HF (CHF) has advanced, refining the areas of diagnosis, risk stratification, prognosis, and treatment is still needed. The natriuretic peptides, specifically B-type natriuretic peptide (BNP) and N-terminal pro-B-type natriuretic peptide (NT-proBNP), have shown promise in clinical practice. Brain natriuretic pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 61 publications
0
16
0
1
Order By: Relevance
“…El futuro de los PN se encuentra en la estratificación del riesgo en otras enfermedades cardiacas, como el síndrome coronario agudo y posiblemente, para determinar la gravedad de las enfermedades valvulares 10,11 .…”
Section: Marcadores Neurohormonalesunclassified
“…El futuro de los PN se encuentra en la estratificación del riesgo en otras enfermedades cardiacas, como el síndrome coronario agudo y posiblemente, para determinar la gravedad de las enfermedades valvulares 10,11 .…”
Section: Marcadores Neurohormonalesunclassified
“…Enhanced gene expression secondary to cardiac wall stress, especially LV wall stress, results in the production and secretion of brain natriuretic peptide (BNP) . Morphological changes may contribute to increased wall stress, possibly leading to elevated BNP levels.…”
Section: Introductionmentioning
confidence: 99%
“…It is secreted by the heart along with biologically active BNP, and is one of the natriuretic peptides [1]. Recent studies have shown that elevated serum NT-pro-BNP is an independent predictor of adverse outcomes from congestive heart failure [2]. In hemodialysis patients, elevated serum NT-pro-BNP is associated with hypervolemia and mortality [34].…”
Section: Introductionmentioning
confidence: 99%